Facing the mountain : a true story of Japanese American heroes in World War II - Brown, Daniel James, 1951- (New York, NY : Random House Large Print, 2021)
Draws on extensive interviews with the families of four soldiers to chronicle the special Japanese-American Army unit that overcame brutal odds in Europe while their parents were forced to surrender their homes and submit to life in concentration camps on American soil.
Prologue -- Shock -- Exile -- Kotonks and buddhaheads -- A thousand stitches -- To the gates of hell -- Home -- Epilogue.
Includes bibliographical references (pages 691-759) and index.
110576
Keywords: United States. -- Army. -- Regimental Combat Team, 442nd.; 1900-1999; World War, 1939-1945 -- Campaigns -- Europe; Japanese American soldiers -- History -- 20th century; World War, 1939-1945 -- Participation, Japanese American; World War, 1939-1945 -- Regimental histories -- United States; Large type books; World War, 1939-1945 -- Campaigns -- Western Front; World War, 1939-1945 -- Campaigns -- Europe; World War, 1939-1945 -- Discrimination -- United States; Large type books; History; Informational works